"Seeing like a Professor" or Shifting Gears: University Temporality and the Pace of Transformation in Post-Soviet Russia. Issue 3 (2nd July 2020) - Saburova, Tatiana
Abstract: Over the past nearly 30 years, Russian universities have been buffeted by external forces necessitating attempts to adjust to a fast-changing academic climate, both globally and regionally. Based on informally structured interviews of university faculty of different age groups and ranks, academic fields and regions of the country conducted between 2012 and 2018, this essay examines what transpires in the life of a Russian university; how do professors evaluate change and how has the pace of university life been altered—such questions are addressed by revealing the connection between notions of academic freedom and temporality—the perceived ability to exert control over time at the university.